2021
DOI: 10.1590/0102-311x00254720
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerabilidades das indústrias nacionais de medicamentos e produtos biotecnológicos no contexto da pandemia de COVID-19

Abstract: Resumo: Em tempos de pandemia, a vulnerabilidade econômica, tecnológica e dos sistemas de saúde fica ainda mais exposta. No Brasil, os maiores desafios são o controle do déficit da balança comercial e a dificuldade de acesso a medicamentos e produtos da saúde ou até mesmo de seu desenvolvimento. A forte dependência externa de insumos e produtos para a saúde é um dos fatores negativos do país no enfrentamento da emergência sanitária mundial ocasionada pelo novo coronavírus SARS-CoV-2. Nesse contexto, o artigo p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 15 publications
0
8
0
7
Order By: Relevance
“…A Brazilian study published in 2021 discussed the vulnerability of national pharmaceutical industries in the context of the pandemic and identified as the main factors for its insufficient production: 1) uncoupling of public policies and industrial policies; 2) dependence on imported active pharmaceutical ingredients (API), since Brazil produces only 10% of the required amount; 3) depreciation of the Brazilian Real relative to the US dollar, increasing the prices of importing ingredients and medicines. These factors, among other aspects and in association with a sudden increase in the demand for anesthetics at hospitals, shortages in national pharmaceutical distributors, and the unpreparedness of public and private entities in face of a situation without precedent in the modern world, contributed to a greater or lesser extent to the variations in prices of medicines in the first two years of the pandemic 10 .…”
Section: Discussionmentioning
confidence: 99%
“…A Brazilian study published in 2021 discussed the vulnerability of national pharmaceutical industries in the context of the pandemic and identified as the main factors for its insufficient production: 1) uncoupling of public policies and industrial policies; 2) dependence on imported active pharmaceutical ingredients (API), since Brazil produces only 10% of the required amount; 3) depreciation of the Brazilian Real relative to the US dollar, increasing the prices of importing ingredients and medicines. These factors, among other aspects and in association with a sudden increase in the demand for anesthetics at hospitals, shortages in national pharmaceutical distributors, and the unpreparedness of public and private entities in face of a situation without precedent in the modern world, contributed to a greater or lesser extent to the variations in prices of medicines in the first two years of the pandemic 10 .…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil, a indústria farmacêutica possui forte predomínio de empresas multinacionais, focadas essencialmente na produção e comercialização de medicamentos, e ainda, a indústria farmacêutica nacional demonstra fragilidade tecnológica e dependência externa de insumos e produtos. Essa dependência externa, aliada a fragilidades estruturais, aumentam a vulnerabilidade para o abastecimento de produtos para a saúde (Fernandes et al, 2021). Além de problemas envolvendo o mercado farmacêutico, fatores como atrasos na entrega pelos fornecedores, escassez de interessados em processos licitatórios, não cumprimento de contrato e desorganização do setor de compras local podem refletir em desabastecimento (Monteiro et al, 2021;Silva & Bandeira, 2022).…”
Section: Dificuldades Na Gestão (N = 4)unclassified
“…34,35 The sudden increase in the consumption of the most used medications and with greater financial impact related to the support and care of the patients selected, according to the unit's consumption record, is associated with the difficulty by the national industrial sector to meet this demand and the difficulties importing products and inputs observed in the pandemic culminated in rising prices. 9,36,37,38 Thus, the importance of structuring and promoting a drug production network in the Brazilian territory was highlighted, with the objective of supplying the internal market, which is strong and less dependent on the world's economy and politics. 9,36,37,38 Most of the medications used by the patients were aimed at preventing opportunistic infections, maintaining homeostasis, induction and maintenance of intubation, and life support.…”
Section: Rbfhssmentioning
confidence: 99%
“…9,36,37,38 Thus, the importance of structuring and promoting a drug production network in the Brazilian territory was highlighted, with the objective of supplying the internal market, which is strong and less dependent on the world's economy and politics. 9,36,37,38 Most of the medications used by the patients were aimed at preventing opportunistic infections, maintaining homeostasis, induction and maintenance of intubation, and life support.…”
Section: Rbfhssmentioning
confidence: 99%